INVENTARISASI JENIS-JENIS DAN PEMANFAATAN TANAMAN PEKARANGAN OLEH MASYARAKAT DI DESA SUNGAI BANYAK IKAN SEBAGAI RANCANGAN BUKU SAKU UNTUK PEMBELAJARAN BIOLOGI SMA - Hardiknas Sari; Yuslim Fauziah; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Research has been carried out which aims to determine the types and benefits of yard plants in Desa Sungai Banyak Ikan and to design a pocket book on the types and uses of yard plants by the community in Desa Sungai Banyak Ikan for high school biology learning. The research was conducted in the community yard of Desa Sungai Banyak Ikan and the PMIPA FKIP UNRI laboratory from March to April 2022. Research data collection was carried out through a preliminary study to the field to determine the state and enviromental conditions in the research location, direct observation to each resident’s house that was used as the research location, interviews with residents, and identification of yard plants. The result of the study were used to design a Biology pocket book for high school students. This handbook is designed for biodiversity materials. The design of the pocket book was carried out in April 2022 until the data collection stage. There are two stages of pocket book design research, namely the analysis stage and the design stage. The analysis phase consists of curriculum analysis and subject material analysis. The design steg includes making lesson plans and designing a pocket book. The conclusions obtained from the results of an inventory of the types and benefits of yard plants by the Desa Sungai Banyak Ikan community as a pocket book design for high school biology learning are the types of plants found around the residents’ yards, namely 20 types of ornamental plants, 5 types of medicinal plants, 23 types of fruit plants, 6 types of spice plants, and 7 types of vegetable plants. In addition, a pocket book design is producet that can be used as an additional reference for Biology learning, especially biodiversity material.Key Words: Yard Plants, Desa Sungai Banyak Ikan, Pocket Book